PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN SUSTAINABILITY REPORT SEBAGAI VARIABEL MEDIASI - Ayu Nur Fadillah; Endah Susilowati (Fakultas Ekonomi Universitas IBA, 2023)
The aim of this study was to analyze company size on firm value with sustainability report as a mediating variable in Manufacturing Companies in various industrial fields listed on the Indonesia Stock Exchange for the 2019-2021 period. A study was conducted in Manufacturing Companies in various industrial sub-sectors because in recent years there has been a decline in stock prices and the problem of hazardous waste pollution due to the company's operational activities. This research uses quantitative methods. There are 56 manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange for the 2019-2021 period which are the population in this study. The purposive sampling technique was used to select the sample, and 36 companies were obtained. Hypothesis testing was carried out using SEM-PLS. This study shows that company size has a significant effect on sustainability reports, company size has a significant effect on firm value, and sustainability reports cannot mediate the relationship between company size and firm value.